'I prefer 30°'?: Business strategies for influencing consumer laundry practices to reduce carbon emissions. (20th July 2018) - Morgan, Elizabeth; Foxon, Timothy J.; Tallontire, Anne
Abstract: This paper analyses businesses' initiatives to influence consumption carbon emissions in home laundering, principally by persuading consumers to wash clothes at lower temperatures. A number of voluntary business initiatives have sought to change consumer practices, coming from detergent manufacturers, their industry association and retailers. This paper analyses their impact at system level, by assessing the coevolutionary interactions between 'Supply', from consumer-facing firms, whose principle business is to sell products to consumers, both manufacturing and retailing, and 'Demand' from consumers, whose interactions with the businesses arise from shopping, using and receiving consumer messages from the firms. The research analyses the interactions between the business case drivers for presentation of consumer messages to reduce laundry emissions and the drivers of changes in consumer laundry practices. This enables inductive inference of the causal relationships over time between businesses' strategies to communicate with consumers and changes in users' laundry temperatures. The paper concludes that, in spite of considerable efforts and resources, these business initiatives have not resulted in the intended level of change in consumer practice that would deliver significant emissions reductions. Consumption emissions from households are a result of interdependent systems of provision, technologies and infrastructure, so stronger actions by business to influence consumer practices as well as further regulatory drivers are likely to be needed to deliver stricter emission reduction targets. This research contributes to the field of sustainable consumption through bringing together a coevolutionary framework with theories of business model innovation and social practices, in order to analyse whole systems of competing businesses' strategies in context with technologies, institutions and ecosystems.